2017
DOI: 10.1007/s00192-017-3473-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing exercises recommended for women at risk of pelvic floor disorders using multivariate statistical techniques

Abstract: No differences in IAPs were found between the recommended and discouraged versions of the same exercise for all exercise types. In particular, the IAPs generated during the two versions of ball rotations, lunges, core, push-ups and squats did not differ significantly. Performing the recommended pelvic floor "safe" version instead of the discouraged conventional version of these exercises may not necessarily protect the pelvic floor and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
2
4
0
2
Order By: Relevance
“…As expected, in the present study the increase in IAP was minimal during PFM contractions and higher during abdominal curl‐ups and cough. This is broadly in agreement with results of other studies using manometry and dynamometers . Neumann and Gill (2002) measured IAP with a sensor made of fluid‐filled silicon positioned in the posterior fornix of the vagina in four participants.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As expected, in the present study the increase in IAP was minimal during PFM contractions and higher during abdominal curl‐ups and cough. This is broadly in agreement with results of other studies using manometry and dynamometers . Neumann and Gill (2002) measured IAP with a sensor made of fluid‐filled silicon positioned in the posterior fornix of the vagina in four participants.…”
Section: Discussionsupporting
confidence: 88%
“…During other exercises, Newmann and Gill reported the mean IAP was 27 mmHg (range 11‐34) during abdominal crunch, 36 mmHg (range 33‐52) during forced expiration, and 46 mmHg (37‐55) during cough . Tian et al (2016) reported a mean IAP of 17.25 mmHg during a curl‐up . Our results measured a significantly lower IAP during curl‐up 8.8 mmHg (±7.33) and expiration 6.12 mmHg (±4.91), but a comparable increase during a cough 40.99 mmHg (±7.33) suggesting that the previous measurements may have included both PFM activation and abdominal pressure measurements.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Examples of IAPs during dynamic activities and abdominal training are summarized in Tables 1 and 2. In an interesting study challenging the widely held belief that pelvic floor "safe" exercises generate lower IAPs than corresponding conventional exercises, no differences in IAPs were found between the recommended and discouraged versions of half the exercises, including ball rotations, lunges, core, push-ups and squats [30]. Others have also pointed out that activities generally restricted after surgery may generate lower IAPs than unrestricted activities.…”
Section: How Do Specific Exercises Influencementioning
confidence: 91%
“…14 Um outro estudo comparou a PIA durante exercícios 'normais' com planos alternativos considerados seguros para o pavimento pélvico e não encontrou diferenças significativas. 45 Na mesma revisão, 14 os autores propõem que a PIA possa ter impacto nos MPP não pelo seu valor absoluto de carga sobre o pavimento pélvico mas por esta ser aplicada repetidamente e com carácter dinâmico.…”
Section: Discussionunclassified